Determinants of poor mental health of medical students in Portugal—A nationwide study - D’Alva-Teixeira, Vânia (2023)
The study was conducted in accordance with the Declaration of Helsinki, and approved by the Ethics Committee of University of Minho (protocol code CEICVS 064/2015) on 30 May 2022.